Interv'iu s Ministrom topliva i energetiki RF . Interv'iu s Ministrom topliva i energetiki RF . Interview with the Minister of Energy of the Russian Federation . Интервью с Министром топлива и энергетики РФ - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Energy Minister IUrii Shafranik's business trip to the Komi Republic. Featured in the program: Shafranik, IUrii Konstantinovich (Minister of Fuel and Energy of the Russian Federation) Поездка Министра топлива и энергетики Юрия Шафраника по территории республики Коми. В программе участвуют: Шафраник, Юрий Константинович (Министр топлива и энергетики Российской Федерации)